Book Reviews (Blackfriars, 1926)
Book Reviews in this Article The History of Witchcraft and Demonology. By Montague Summers. Debits and Credits. By Rudyard Kipling. The World of William Clissold. Books III and IV. Short Talks with the Dead and Others. By Hilaire Belloc. Mrs. Markham's New History of England. By Hilaire Belloc. The Reformation in Dublin, 1536–1558. By Myles V. Ronan, C.C. Edward Thring: Maker of Uppingham School. By W. F. Rawnsley. Mr. Belloc Objects to‘The Outline of History.’By H. G. Wells. Life of St. Philip Neri. By Cardinal Capecelatro. Translated by Thomas Alder Pope of the Oratory. Richard Luke Concanen, O.P., First Bishop of New York. By Vincent R. Hughes, O.P. The Shadow on the Earth. By Owen Francis Dudley. The Names of Christ. Readings from Nombres de Cristo. By Fray Luis de Leon. Translated from the Spanish by a Benedictine of Stanbrook. With a preface by Father Benedict Zimmerman, O.C.D. Treatise on Prayer and Meditation. By Saint Peter of Alcantara. Translated by Dominic Devas, O.F.M. Together with a complete English version of Pax Animae by John of Bonilla. The Divine Song Book. A Brief Introduction to the Psalms. By Stephen J. Brown, S.J. From Holy Communion to the Blessed Trinity. By M. V. Bernadot, O.P. Translated by Dom Francis Izard, O.S.B.